Abdomen/pelvis computed tomography in staging of pediatric Hodgkin Lymphoma: is it always necessary?. (3rd August 2016) - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Terenziani, Monica; Mura, Rosamaria; D'Amico, Salvatore; Casini, Tommaso; Mosa, Clara; Pillon, Marta; Boaro, Maria Paola; Bottigliero, Gaetano; et al.
Abstract: The purpose of the study was to determine if abdomen/pelvis computed tomography (CT) can be safety omitted in the initial staging of a subgroup of children affected by Hodgkin Lymphoma (HL). Every participating center of A.I.E.O.P (Associazione Italiana di Ematologia ed Oncologia Pediatrica) sent local staging reports of 18F‐fluorodeoxyglucose positron emission tomography (PET) and abdominal ultrasound (US) along with digital images of staging abdomen/pelvis CT to the investigation center where the CT scans were evaluated by an experienced pediatric radiologist. The local radiologist who performed the US was unaware of local CT and PET reports (both carried out after US), and the reviewer radiologist examining the CT images was unaware of local US, PET and CT reports. A new abdominal staging of 123 patients performed on the basis of local US report, local PET report, and centralized CT report was then compared to a simpler staging based on local US and PET. No additional lesion was discovered by CT in patients with abdomen/pelvis negativity in both US and PET or isolated spleen positivity in US (or US and PET), and so it seems that in the initial staging, abdomen/pelvis CT can be safety omitted in about 1/2 to 2/3 of children diagnosed with HL. Abstract : We decided to verify if there was an overadministration of staging computed tomography (CT) in pediatric HL. A new staging of 123 patients performed on the basis of local US report, local PET report, and centralized CT report was compared to a simpler staging based on local US and PET. No additional lesion was discovered by CT in patients with abdomen/pelvis negativity in both US and PET or isolated spleen positivity in US (or US and PET).